2013
DOI: 10.1088/0031-9155/58/8/2523
|View full text |Cite
|
Sign up to set email alerts
|

The role of gas in ultrasonically driven vapor bubble growth

Abstract: In this paper we study both experimentally and theoretically the dynamics of an ultrasound-driven vapor bubble of perfluoropentane (PFP) inside a droplet of the same liquid, immersed in a water medium superheated with respect to the PFP boiling point. We determine the temporal evolution of the bubble radius with ultra-high speed imaging at 20 million frames per second. In addition, we model the vapor-gas bubble dynamics, based on a Rayleigh-Plesset-type equation, including thermal and gas diffusion inside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 29 publications
(35 reference statements)
0
64
0
Order By: Relevance
“…5 The proposed mechanism contradicted results suggesting that onset of ADV originates within the droplet and is cavitation independent. 2,16,17 More recently, Shpak et al observed the nucleation process in single and double emulsion PFC droplets where in the latter case consistent localization of vaporization was observed, originating at 0.4 R away from the center of the droplet along the axis of the ultrasound, where R is the droplet radius. 18,19 The goal for this study is to directly visualize the nucleation site formation in liquid PFC microdroplets due to the ADV process and propose a potential mechanism initiating vaporization.…”
mentioning
confidence: 82%
“…5 The proposed mechanism contradicted results suggesting that onset of ADV originates within the droplet and is cavitation independent. 2,16,17 More recently, Shpak et al observed the nucleation process in single and double emulsion PFC droplets where in the latter case consistent localization of vaporization was observed, originating at 0.4 R away from the center of the droplet along the axis of the ultrasound, where R is the droplet radius. 18,19 The goal for this study is to directly visualize the nucleation site formation in liquid PFC microdroplets due to the ADV process and propose a potential mechanism initiating vaporization.…”
mentioning
confidence: 82%
“…The acoustic driving pulse was delivered from an arbitrary waveform generator (Tabor 8026; Tabor Electronics) amplified by an rf amplifier (ENI 350L; Electronic Navigation Industries, Inc.). Droplet samples were vaporized with a single ultrasound pulse, consisting of a burst between 6 and 10 cycles and a driving pressure with a peak negative pressure P − inc = − 4:5 MPa at 45°angle to the horizontal OptiCell plane (22,24). The pressure value was calibrated in the same setup at the position of the droplets using a 0.2-mm PVDF probe hydrophone (DC27/000658; Precision Acoustics Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…The acoustic pressure amplitudes required to nucleate the droplet have been observed to be very high. In a typical ADV experiment, before impinging on the droplet the ultrasound wave from a focused transducer travels a distance on the order of a few centimeters (7,(17)(18)(19)(22)(23)(24). Under these conditions the wave that arrives at the focus of the transducer can be highly distorted owing to nonlinear propagation (25,26).…”
Section: Significancementioning
confidence: 99%
“…But the noncondensable gas does not contract as a result leaving an extremely small gas bubble that will contribute to form a larger bubble on the next acoustic cycle. This process has been observed [56] and helps to manifest that the size of gas bubbles after cessation of ultrasound irradiation is much bigger than the size expected in the initial PFC droplets [57,58].…”
Section: Bubble Growthmentioning
confidence: 53%